Объяснение:
A)(x-1)(x-4)=0
x^2+4x-x-4=0
x^2+3x-4=0
Д=9+16=25=5^2
X1oe,2oe=(-3+-5)/2
x1=1
x2=-4
Б) (x+4)(2x-1)=0
2x^2-x+8x-4=0
2x^2+7x-4=0
Д=49+32=81=9^2
X1ое,2ое=(-7+-9)/4
x1=1/2=0,5
x2=-4
В) (6-x)(5-2x)=0
30-12x-5x+2x^2=0
2x^2-17x+30=0
Д=289-240=49=7^2
X1oe,2oe=(17+-7)/4
X1=2,5
X2=6
1. а) 4^6*3^8:12^5=(4^6*3^8)/(3^5*4^5)=4*3^3=4*27=108
б) ((a^23)*(a^-8))/a^16=a^-1=1/a
при а=0,04
1/a=1/0,04
в) (b^1/5)*((b^4/10)^2)=b^1=b
г) (7^(корень из 3))*(7^2-(корень из 3))=7^2=49
д) ((15^12)^3):(5^37)=(5^36):(5^37)=5^-1=1/5
е) ((8*корень из 11)^2)/88=(64*11)/88=8
ж) (b^1/3)*((b^5/6)^2)=(b^1/3)*(b^5/3)=b^2
3. а) ((2a^3)^4):(2a^11)=(16a^12)/(2a^11)=a
б) (Корень 3-ей степени из (ab^2)/c)*(корень 3-ей степени из (a^5b)/c^2)=Корень 3-ей степени из (a^6b^3)/c^3=(a^2b)/c
в) ((2^(корень из 2)-1)*(2^(корень из 2)-1)):(корень из 2)=(2^2-(корень из 2))*(2^2+(корень из 2))=2^4=16
4. а) 7^(корень из 3) и (0,7)^(корень из 3)
7>0,7
7^(корень из 3)>(0,7)^(корень из 3)
б) (0,012)^-3 и 1
(0,012)^-3 и 1^-3
1=1^-3
0,012<1
(0,012)^-3<1
1) 8х + 1,3 = 34,9 - 8х 2) -4 = -2/8х
8х + 8х = 34,9 - 1,3 х = -4 : (-2/8)
16х = 33,6 х = 4 · 8/2
х = 33,6 : 16 х = 2 · 8
х = 2,1 х = 16
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3) 9х = 108 4) 6х - 8 = 6,4
х = 108 : 9 6х = 6,4 + 8
х = 12 6х = 14,4
х = 2,4
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
5) 4(х - 2) = -1 6) 40х = -32
4х - 8 = -1 х = -32 : 40
4х = 8 - 1 х = -0,8
4х = 7
х = 7/4
х = 1 целая 3/4 = 1,75 (в десятичных дробях)
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
7) 4х - 2 = 22 8) 5х - 13 + 2(3 - х) = -х + 16
4х = 22 + 2 5х - 13 + 6 - 2х = -х + 16
4х = 24 5х - 2х + х = 16 - 6 + 13
х = 24 : 4 4х = 23
х = 6 х = 23/4 = 5 целых 3/4 = 5,75
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
9) 4(3х + 5) - 3(4х - 1) = 22х + 12
12х + 20 - 12х + 3 = 22х + 12
12х - 12х - 22х = 12 - 3 - 20
-22х = -11
х = -11 : (-22)
х = 1/2 = 0,5 (в десятичных дробях)
Объяснение:
а) ( х-1 )(х+4) = 0
ответ.(1;-4)
б) ( х+4 )(2х-1) = 0
ответ.(1/2;-4)
в) ( 6-х)(5-2х) = 0
ответ.(6;2,5)
г) ( 2+5у)(2у+7) = 0
ответ. (-2/5;-3,5)
д) -2х(х-3) = 0
ответ.(0;3)
у(3у+9) = 0
ответ.(0;-3)